Experimental Research on the JT Cycle of Hybrid 4.5K JT Cryocooler. (April 2019) - Ma, Yuexue; Quan, Jia; Wang, Juan; Liu, Yanjie; Li, Jianguo; Liang, Jingtao
Abstract: Key Laboratory of Space Energy Conversion Technologies of TIPC, CAS has developed a 4.5K Joule-Thomson (JT) cryocooler precooled by a multistage pulse tube cooler. In this paper, series of experimental research is carried out to explore the performance of the JT cooler at different operating conditions. When only the power consumption of JT compressors is considered, the coefficient of performance (COP) of the JT cycle is proposed to evaluate the performance of JT cycle. Experimental research is carried out to investigate the influence of supply pressure and JT orifice on cooling capacity and especially the COP of JT cooler. Experimental results suggest that cooling power of JT cooler increases as supply pressure increases and higher COP are gained because of rising flow resistance of JT orifice. Then JT orifices of different diameters are experimentally studied to explore the effect of flow resistance of JT orifice on the performance of JT cooler.